A new perspective: Exploring future therapeutic strategies for cancer by understanding the dual role of B lymphocytes in tumor immunity. Issue 12 (26th November 2018) - Liu, Min; Sun, Qian; Wang, Jian; Wei, Feng; Yang, Lili; Ren, Xiubao
Abstract : Our previous understanding of the role of B lymphocytes in tumor immunity is its antitumor effects. However, further evidence indicates B lymphocytes can also promote tumorigenesis by modulating immune responses. Therefore, the increasingly complex role of B lymphocytes in tumor immunity may become an important factor in tumor immunotherapy. In this review, we describe the development of B cells in tumor microenvironments. We then focus on the most controversial issues of the biological functions of B lymphocytes. Finally, we nominate B cells as therapeutic targets, which should open broad perspectives for the development of their clinical applications.